Proceedings of an international conference held ... under the auspices of the Committee on Protein Malnutrition, Food and Nutrition Board and the Nutrition Study Section, National Institutes of Health (Washington, 1961)
The food and nutrition board is most grateful to the National Institutes of health for the support and participation of the nutrition study section which made possible this important conference and the opportunity it provides for evaluating the progress made throigh the cooperative efforts of a notable group of workers and organizations, and for glimpsing the areas where further work is needed.
Keywords: Children,Trẻ em; Nutrition,Dinh dưỡng